2016
DOI: 10.1118/1.4938411
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance evaluation of automated segmentation methods of hippocampus from magnetic resonance images of temporal lobe epilepsy patients

Abstract: The ABSS method for automated hippocampal segmentation outperformed other methods, best approximating what could be achieved by manual tracing. This study also shows that four categories of input data can cause automated segmentation methods to fail. They include incomplete studies, artifact, low signal-to-noise ratio, and inhomogeneity. Different scanner platforms and pulse sequences were considered as means by which to improve reliability of the automated methods. Other modifications were specially devised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Previous studies reported that earlier versions of FreeSurfer agree more closely with manual methods than other common tools, FSL/FIRST [Morey et al, 2009; Schoemaker et al, 2016] or IBASPM [Tae et al, 2008]. Some hippocampus-specific classification systems [Tangaro et al, 2014; Platero and Tobar, 2016] and the Automatic Brain Segmentation System [Hosseini et al, 2016] have outperformed FreeSurfer in hippocampus-specific segmentations. FreeSurfer has also been shown to be more sensitive to the atrophy coincident with MDD than alternatives [Morey et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that earlier versions of FreeSurfer agree more closely with manual methods than other common tools, FSL/FIRST [Morey et al, 2009; Schoemaker et al, 2016] or IBASPM [Tae et al, 2008]. Some hippocampus-specific classification systems [Tangaro et al, 2014; Platero and Tobar, 2016] and the Automatic Brain Segmentation System [Hosseini et al, 2016] have outperformed FreeSurfer in hippocampus-specific segmentations. FreeSurfer has also been shown to be more sensitive to the atrophy coincident with MDD than alternatives [Morey et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral mesial temporal lobe atrophy raises concerns of markedly reduced chance of seizure freedom after surgery 76 and an increased risk of memory impairment. 14 Over the years, steady technical advances have propelled the design of automated algorithms yielding segmentation of the whole hippocampus (eg, Sone et al, 77 Hosseini et al, 78 Kim et al 79 ), and more recently hippocampal subfields, 80 thereby creating a solid basis for broad translation ( Figure 5). Several US Food and Drug Administration (FDA)-approved commercial software packages are currently available for routine use in clinical practice and provide an automated report that details the volume and percentile of each parcellated cortical region compared to a normative database.…”
Section: Volumetry and Shape Modeling Of Mesiotemporal Lobe Structuresmentioning
confidence: 99%
“…Hosseini et al provided a comprehensive evaluation of the hippocampus segmentation algorithms [Hosseini et al, ]. They categorize various metrics into three groups.…”
Section: Introductionmentioning
confidence: 99%
“…The three groups of metrics base their evaluation on, respectively, voxel, distance, and volume. To better characterize the segmentation with and without the super resolution scheme, we also compute the evaluation metrics in [Hosseini et al, ], shown in Table .…”
Section: Introductionmentioning
confidence: 99%